Mudflat facies in the lower part of Nanggulan Formation, Kulon Progo Mountain, Yogyakarta, Indonesia - Nuraini, siti (ReTII, 2025)
The mudflat facies type is commonly interpreted as layered parallel limestone mudstone with horizontal bedded located near the coastline. However, the current mechanics and feeder systems are often found in its interbeds in very fine to medium-grained sandstone lithology. This study will investigate the mudflat facies type of the Nanggulan Formation with interbeds of very fine to fine-grained sandstone and calcilutite limestone lithology. The method used is to create a vertical stratigraphic sections of the Nanggulan Formation using Watupuru river. Sedimentary structures found indicate the role of tidal current mechanics such as heterolithic, herringbone, mud drapes, neap and spring interbedding, double mud lamination, and wrinkled lamination. Ichnofossils also vary in this facies. The river distribution system is controlled by two different sources, from the land and the sea, formed simultaneously in the intertidal zone.